Development of a Centralized Electronic Lock System Based on 3G Broadband Modules - Abate, Abdi; Rutgersson, Patrik (My University, 2012)
Ericsson’s 3G Broadband modules are primarly intended for laptops, but they are perfect in terms of size for being used in other electronic devices. Therefore, the purpose of this master’s thesis is to develop a demo system for Ericsson’s 3G Broadband modules. We have developed an electronic lock system consisting of a large number of access points talking to a centralized server. The server handles the access control and is contacted everytime a user wants to get access to an electronic lock. The electronic locks, called access points, need 3G modules to be able to communicate with the server over the Internet. The communication within the system is encrypted with SSH and pin codes are used to identify different users. The developed system became a well-functional electronic lock system.
Keywords: Information Technology; Informationsteknik